From marketing research to communication strategy: account planning in Portuguese advertising Agencies / Paulo Ribeiro Cardoso (Faculty of Business and Management ; UiTM Press, 2006)
To develop and perform a creative strategy for a campaign, advertising agencies must search for process, and deliver information. In this article, we argue that the information considered more important by the agency professionals does not always correspond to the one that is more frequently searched for and delivered inside the advertising agency. In order to verify this proposition, we undertook a mail survey with a sample of 265 Portuguese advertising agency professionals during the Summer 2002. After the presentation of the findings, the limitations of the present study and the suggestions for further research are discussed.